2015
DOI: 10.1139/cjfr-2015-0044
|View full text |Cite
|
Sign up to set email alerts
|

Use of depth-first search and direct search methods to optimize even-aged stand management: a case study involving maritime pine in Asturias (northwest Spain)

Abstract: Maritime pine (Pinus pinaster Ait.) is one of the most important timber species in Asturias and more generally in northwest Spain. A dynamic growth model has recently been developed for this species and region, allowing computation of the merchantable volume by two alternative methods: a disaggregation system and a stand volume ratio function. The model enables optimization of the management schedule for the species by modifying the rotation age and the number, intensity, and timing of thinning operations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…For stand-level optimization, there are various different algorithms to choose from [35,36], e.g., the derivative-free direct search method such as the Hooke and Jeeves method, differential evolution, particle swarm optimization [37], hybrid optimization strategies which combine separate algorithms (e.g., [16]) or depth-first search algorithms which apply a search tree consisting of a backtracking mechanism [37]. In this study, we applied a new algorithm which has recently been introduced to forest applications: sequential quadratic programming (SQP) [38].…”
Section: Discussionmentioning
confidence: 99%
“…For stand-level optimization, there are various different algorithms to choose from [35,36], e.g., the derivative-free direct search method such as the Hooke and Jeeves method, differential evolution, particle swarm optimization [37], hybrid optimization strategies which combine separate algorithms (e.g., [16]) or depth-first search algorithms which apply a search tree consisting of a backtracking mechanism [37]. In this study, we applied a new algorithm which has recently been introduced to forest applications: sequential quadratic programming (SQP) [38].…”
Section: Discussionmentioning
confidence: 99%
“…Although the election of a proper method for stand-level optimization is problem-dependent (Pukkala 2009;AriasRodil et al 2015), the Hooke and Jeeves' method has always shown competitive performance when compared with other stand-level optimization methods, e.g., population-based methods and ''depth-search first'' method (Pukkala 2009;García-Gonzalo et al 2014;Arias-Rodil et al 2015). In our case, where a stochastic model was in the optimal schedules for Stands 1 and 2 with different cone prices (0, 0.1, 0.3 and 0.5 € ha -1 ) when discount rate is 3 % Eur J Forest Res used, results from Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the huge number of alternatives, optimization was used to find the best possible values for the parameters of the CA. The method used was particle swarm optimization (Pukkala 2009;Arias-Rodil et al 2015), which has been found to work well when the number of simultaneously optimized variables is high (Jin et al 2018). A description of the particle swarm optimization algorithm used in this study is presented in Appendix 1 in ESM.…”
Section: Optimizationmentioning
confidence: 99%